Consumer society critical issues and environmental consequences - Smart, Barry; Sage eBooks (Los Angeles, [Calif.] ; London : SAGE, 2010)
Has consumer culture got out of hand? Are the costs of universal access and pollution too great to bear? This lively and informative book brings together resources for thinking about consumer culture and examining its origins and consequences within a global context. It uses examples to inform and enhance understanding.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Consumption (Economics) -- Social aspects; Electronic books